2016
DOI: 10.1007/s10897-016-0036-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Self‐Esteem of Individuals with Neurofibromatosis Type 1 (NF1)

Abstract: Neurofibromatosis Type 1 (NF1) is a progressive genetic disorder characterized by physical findings such as café-au-lait macules, Lisch nodules, and neurofibromas in addition to other medical complications. Learning and social problems are more prevalent among individuals affected with NF1. It has been reported that people with NF1 have lower self-esteem (SE) when compared to the general population. Additionally, a study published over 20 years ago found that overall knowledge of NF1 was lacking in individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…To the best of our knowledge, no studies of adults with NF1 have addressed social support as a main variable. In a recent survey of 73 persons with NF1 aged 13 to 73 years, Rosnau et al (2017) found higher self-esteem among persons who reported they had friends with NF1 and among those who took part in NF1 support groups.…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, no studies of adults with NF1 have addressed social support as a main variable. In a recent survey of 73 persons with NF1 aged 13 to 73 years, Rosnau et al (2017) found higher self-esteem among persons who reported they had friends with NF1 and among those who took part in NF1 support groups.…”
Section: Discussionmentioning
confidence: 94%
“…The same group employed a related intervention of mind–body therapy provided by videoconferencing (Vranceanu et al., 2016), which has similar benefits in terms of improving resiliency (Zale, Pierre‐Louis, Macklin, Riklin, & Vranceanu, 2018). Rosnau et al found that adolescents with NF1 who attended a support group comprised of other similarly affected individuals were associated with higher reported self‐esteem (Rosnau et al., 2017). Studies of an Internet support group for parents of children with NF1 showed this method of support as a feasible and possibly effective option for parental support, and additional studies evaluating qualitative analysis continue (Martin et al., 2016, 2018).…”
Section: Genetic Counseling Processmentioning
confidence: 99%
“…Are clubbed feet associated with NF1? (Benjamin et al, 1993;Rosnau et al, 2017). To our knowledge, this study is the first to identify an association between parental NF1 status and NF1-related knowledge and serves as an important addition to the existing body of research.…”
Section: 6mentioning
confidence: 88%
“…Neurofibromatosis type 1 knowledge items were adapted from questions used in the Benjamin et al (1993), Rosnau et al (2017), and Erblich et al (2005) studies. Additional questions were formulated and reviewed by genetic counselors who specialize in NF1 diagnosis and management.…”
Section: Evaluation Of Nf1 Knowledgementioning
confidence: 99%
See 1 more Smart Citation